ANALISIS KELAYAKAN FINANSIAL DAN DAYA TERIMA INOVASI PRODUK MOCHI NANAS (MONAS) - Safitri, Laras Sirly; Mukminah, Nurul; Rahayu, Wiwik Endah (Lampung University, 2024)
This research aims to analyze the financial feasibility of the pineapple mochi product innovation (Monas) and determine its acceptability based on sensory quality. This research was conducted in May - August 2023 using a quantitative descriptive research design. The financial feasibility of Monas products was analyzed based on the NPV, IRR, Payback Period and R/C ratio values, while acceptability was analyzed using hedonic quality testing on 20 semi-trained panelists. The research results show that Monas product innovation is feasible to be developed with NPV value of IDR 24,505,289.00, IRR value of 51 percent, payback period of 1.79 years, and an R/C ratio value of 1.10. The acceptance of Monas product innovation showed the quality of the bright yellow color, chewy texture, slightly strong aroma typical of pineapple, and the sweet and sour taste typical of pineapple.Keywords: financial feasibility, hedonic quality, pineapple mochi, product innovation